Interaksi Budaya Lokal dan Perubahan Iklim dalam Perspektif Ilmu Lingkungan untuk Memahami Adaptasi Sosial Ekologis Masyarakat Pesisir Nusantara - Dwi Rahayu; Siti Hidayah (CV. Aksara Global Akademia, 2023)
This study aims to analyze the interaction of local culture and climate change from an environmental science perspective, with a focus on the socio-ecological adaptation strategies of coastal communities in the Indonesian archipelago. Climate change has had significant impacts on coastal areas, ranging from increased tidal flooding and coastal erosion to decreased fisheries productivity. In this context, coastal communities rely not only on technical approaches but also utilize local wisdom that has been passed down through generations. The research method used is a qualitative study with an environmental ethnography approach, which allows researchers to explore the relationship between culture, ecology, and environmental adaptation. Data were collected through participant observation, in-depth interviews with traditional leaders, fishermen, and local communities, and analysis of cultural documents covering rituals, customary rules, and traditional ecological practices. Data analysis was conducted thematically to identify adaptation patterns, then compared with technical approaches in environmental studies. The results show that coastal communities in the Indonesian archipelago have various forms of culturally based adaptation that are relevant to the challenges of climate change. For example, the practice of marine sasi in Maluku serves to preserve fishery resources, traditional rituals in Bali support collective ecological awareness, and mutual cooperation (gotong royong) on ​​the coast of Java helps mitigate tidal flooding. These practices demonstrate that local wisdom serves a dual purpose: strengthening social cohesion and sustainably protecting the environment. The study's conclusions confirm that adaptation strategies will be more effective if they integrate local wisdom with science-based technical approaches. This integration not only strengthens ecological resilience but also ensures the socio-cultural sustainability of coastal communities.